PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS KONSUMEN DALAM BERBELANJA PADA E-COMMERCE SHOPEE - Anggri Widia Rahma; Sri Ekowati (Yayasan Insani Mandiri Santani, 2022)
This study aims to determine the effect of service quality andÂ trust on customer loyalty in doing shopping at Shopee E-commerce by students of Muhammadiyah University of Bengkulu, specifically atmanagement study program. This research is a quantitative descriptive study. The object of this research was student of management study program, University of Muhammadiyah Bengkulu. The sampling method used was the accidental sampling technique. The number of respondent in this study is 113 students. In collecting data, the researcher used a questionnaire. The collected data were analyzed using multiple linear regression analysis test and hypothesis testing, namely t-test and f-test. The results of the conducted study show that simultaneously service quality and trust had a positive and significant effect on consumer loyalty. Partally, the both variables service quality and trust, have an effect on consumer loyalty. The better the services provided, the more consumers trust the company so as to create sustainable consumer loyalty. Keywords: Service Quality, Trust and Consumer Loyalty.